Integrated marketing strategy for insured outpatient care at a municipal hospital - Leonardo Jaya Setiadi Tanumiharja; H. Undang Juju Juju; Tita Setiawati (Institute of Computer Science (IOCS), 2026)
Background: Evidence is limited on how municipal hospital management can integrate National Health Insurance demand signals, stakeholder experience, the services marketing mix, digital marketing, and resource constraints into strategic planning for outpatient services. JKN-financed outpatient encounters decreased from 12,324 in 2021 to 11,364 in 2022 (?960; ?7.79%), although total outpatient encounters increased from 18,760 to 19,445; counts represent encounters rather than unique patients. Objective: To develop an evidence-linked marketing strategy for JKN outpatient services at a municipal hospital. Methods: This qualitative single-case study integrated hospital documents, 2020–2022 administrative data, interviews, observations, and a focus group using a framework matrix, the seven-part services marketing mix, and weighted SWOT/TOWS analysis. The sample comprised 15 unique participants: three managers and 12 adult JKN outpatients. Results: Accreditation, competent personnel, location, and JKN eligibility were strategic assets. Referral complexity, restricted hours, parking, registration, pharmacy flow, fragmented information systems, and limited digital communication constrained access. Findings supported positioning based on dependable, inclusive care; phased service, referral, and digital initiatives are author-generated proposals requiring prospective evaluation. Conclusion: The study contributes an integrated planning framework but cannot attribute the observed decline to marketing. Future multicentre longitudinal studies should evaluate clinic-level demand, patient experience, waiting times, reimbursement, and incremental costs